Hydrogen‐Bonded Polymer–Small Molecule Complexes with Tunable Mechanical Properties. Issue 9 (13th March 2018) - Liu, Tianqi; Peng, Xin; Chen, Ya‐Nan; Bai, Qing‐Wen; Shang, Cong; Zhang, Lin; Wang, Huiliang
Abstract: A novel type of polymeric material with tunable mechanical properties is fabricated from polymers and small molecules that can form hydrogen‐bonded intermolecular complexes (IMCs). In this work, poly(vinyl alcohol) (PVA)–glycerol hydrogels are first prepared, and then they are dried to form IMCs. The tensile strengths and moduli of IMCs decrease dramatically with increasing glycerol content, while the elongations increase gradually. The mechanical properties are comparable with or even superior to those of common engineering plastics and rubbers. The IMCs with high glycerol content also show excellent flexibility and cold‐resistance at subzero temperatures. Cyclic tensile and stress relaxation tests prove that there is an effective energy dissipation mechanism in IMCs and dynamic mechanical analysis confirms their physical crosslinking nature. FTIR and NMR characterizations prove the existence of hydrogen bonding between glycerol and PVA chains, which suppresses the crystallization of PVA from X‐ray diffraction measurement. These PVA–glycerol IMCs may find potential applications in barrier films, biomedical packaging, etc., in the future. Abstract : A novel type of polymeric material with tunable mechanical properties from plastics to rubber‐like materials is fabricated from polymers and small molecules that can form hydrogen‐bonded intermolecular complexes (IMCs). The mechanical properties of the poly(vinyl alcohol)–glycerol IMCs are comparable with or even superior to those of common engineering plastics and rubbers.